ANALISIS PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA DAN KINERJA KARYAWAN PADA PT. SUKANDA DJAYA PEKANBARU - Sesariani Novita; Marhadi Marhadi; Promalessy Rika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted at PT. Sukanda Djaya Pekanbaru. This study aims to determine how the effect of compensation and work motivation on discipline and employee performance at PT. Sukanda Djaya Pekanbaru. This research is population research. The number of samples in this study were 90 respondents. The analytical method used in this study is the path analysis method (path) using SPSS version 26. The results of this study indicate that compensation has a direct positive effect on the performance of employees of PT. Sukanda Djaya Pekanbaru. This can be seen from the path value of 0.213 which is positive. The work discipline in this research model does not mediate the relationship between compensation and the performance of employees of PT. Sukanda Djaya Pekanbaru. This is due to the value of the direct effect is greater than the indirect effect (0.213> 0.0836). Work motivation has a direct positive effect on the performance of employees of PT. Sukanda Djaya Pekanbaru. This is seen from the path value of 0.289 which is positive. Work discipline in this research model does not mediate the relationship between work motivation and the performance of employees of PT. Sukanda Djaya Pekanbaru. This is due to the value of the direct effect is greater than the indirect effect (0.289> 0.0974). Work discipline has a direct positive effect on the performance of the employees of PT. Sukanda Djaya Pekanbaru. This can be seen from the path value of 0.220 which is positive..Keywords: Compensation, Work Motivation, Work Discipline and Performance